Amoxycillin levels in sputum, serum, and saliva. Issue 1 (January 1974) - Stewart, Sheila M.; Anderson, Isobel M. E.; Jones, G. R.; Calder, Margaret A.; Pratt, C.; Malcolm, Margaret G. G.
Abstract : Stewart, Sheila M., Anderson, Isobel M. E., Jones, G. R., and Calder, Margaret A. (1974). Thorax, 29, 110-114. Amoxycillin levels in sputum, serum, and saliva. The levels of amoxycillin in sputum, saliva, and serum from 22 patients were estimated. Fifteen patients had pneumonia and seven had acute exacerbations of chronic bronchitis. The drug was given orally in a dose of 500 mg four times daily. There was considerable variation in the levels in specimens from different patients. The mean sputum levels two to three hours and six hours after the dose were 0·52 and 0·53 μg/ml respectively. The mean two-hour saliva level was 0·32 μg/ml. The mean serum levels two and six hours after the test dose were 11·0 and 3·5 μg/ml respectively. The higher levels of amoxycillin were usually associated with the presence of more pus in the sputum. The mean levels of amoxycillin at comparable times were significantly greater than those found in a previous study after the same dose of ampicillin. Clinical response to treatment occurred more rapidly in those patients with sputum levels of 0·25 μg amoxycillin per ml or above than in those with lower levels. The time taken to clear potential pathogens from the sputum was related to the pathogen rather than to the amoxycillin level, Haemophilus influenzae persisting for longer than Streptococcus pneumoniae.